Cobbia bengalensis sp. nov. (Xyalidae: Monhysterida) from an eroding island of Sundarban, India - Datta, Tridip Kumar; Bhowmik, Moumita; Choudhury, Amalesh (Zootaxa, 2018)
A new species, Cobbia bengalensis sp. nov., of free-living marine nematodes is described from an island of Sundarban, Indian coast and compared with other eight valid species of the genus. Cobbia bengalensis sp. nov. is characterized and differentiated from the others by a unique combination of sexually dimorphic tail, arrangement of anterior sensilla, amphid position, presence of four subcephalic sensilla at the level of amphid, buccal cavity with one dorsal and two subventral teeth, elongated cardia and the shape of gubernaculum. Some previously recorded taxa thought to be the species of Cobbia has also been discussed. Wrongly recorded data for nematofaunal inventory from Indian water has also been criticized.